2020
DOI: 10.1093/nsr/nwaa065
|View full text |Cite
|
Sign up to set email alerts
|

4D spinless topological insulator in a periodic electric circuit

Abstract: According to the mathematical classification of topological band structures, there exist a number of fascinating topological states in dimensions larger than three with exotic boundary phenomena and interesting topological responses. While these topological states are not accessible in condensed matter systems, recent works have shown that synthetic systems, such as photonic crystals or electric circuits, can realize higher-dimensional band structures. Here, we argue that the 4D spinless topological insulator,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 52 publications
(27 reference statements)
0
56
0
Order By: Relevance
“…Since this proposal was put on arXiv, it has been experimentally implemented in electric circuits [59]. Theoretical proposals have also been made for electric circuits to realise a different spinless (Class AI) 4DQH model [60], to simulate nth-Chern-number insulators [61] and to image nodal boundary Seifert surfaces in 4D circuits [62].…”
Section: Discussionmentioning
confidence: 99%
“…Since this proposal was put on arXiv, it has been experimentally implemented in electric circuits [59]. Theoretical proposals have also been made for electric circuits to realise a different spinless (Class AI) 4DQH model [60], to simulate nth-Chern-number insulators [61] and to image nodal boundary Seifert surfaces in 4D circuits [62].…”
Section: Discussionmentioning
confidence: 99%
“…Circuit metamaterials have been the subject of recent theoretical and experimental interest [28][29][30][31][32][33][34][35][36][37][38][39][40] due to the ease with which they can be designed and fabricated to realize different topological phases, as well as unusual lattice configurations that are hard to achieve on other platforms. Circuits have been used to demonstrate nonlinear topological boundary states [33,34], topological corner modes [35][36][37][38], and four-dimensional topological insulators [39,40]. Most notably, Jia et al [7] have shown how a Haldane-type Chern insulator phase can be accessed using a lattice of capacitors (C) and inductors (L) with braided interconnections.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, Jia et al [7] have shown how a Haldane-type Chern insulator phase can be accessed using a lattice of capacitors (C) and inductors (L) with braided interconnections. Although LC circuits are time-reversal symmetric, the braiding decomposes the spectrum into two degenerate decoupled sectors that are individually T-broken [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], with the physical T symmetry mapping each sector to the other. Utilizing this idea, we design and fabricate a braided LC circuit lattice that realizes the modified Haldane model.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical circuits are ideally suited for transcending the abovementioned challenges, since electronic components, which have benefitted from industrial refinement over the decades, can accommodate almost any desired features like arbitrary long-range connectivity, dimensionality, non-Hermiticity gain/loss as well as non-reciprocity. Recently, simulating topological states with electric circuits has attracted lots of interests based on the similarity between circuit Laplacian and lattice Hamiltonian [23][24][25][26][27][28][29][30]. Some topological states have been observed in circuit networks [31][32][33][34][35].…”
mentioning
confidence: 99%